Prevalence and associated risk factors of Toxoplasma gondii in female farmworkers of southeastern Turkey - Nebiye Yentur Doni; Zeynep Simsek; Gulcan Gurses; Fadile Yildiz Zeyrek; Canan Demir (Journal of Infection in Developing Countries)
Introduction: There are a limited number of studies of the agricultural population about the prevalence of Toxoplasma gondii (T. gondii) infection throughout the world. The aim of this study was to determine the prevalence and risk factors of toxoplasmosis in female farmworkers in the southeastern region of Turkey. Methodology: The optimum sample size was determined using the Epi Info Program, and blood samples were collected from 684 women of reproductive age. Serum samples were analyzed by qualitative and quantitative methods for anti-T. gondii IgG and IgM antibodies with a commercially available enzyme immunoassay. Questionnaires through which socio-demographic information was collected were applied during face-to-face interviews of subjects who gave their consent to participate in the study. Crude odds ratios (ORs) and 95% confidence intervals (CIs) were calculated, and Chi-square analyses and logistic regression were performed. Results: Of the 684 women, the prevalence of toxoplasmosis was determined to be 58.3% and 1% for IgG and IgM, respectively. Employment as a seasonal farmworker, increasing age, and having had three or more pregnancies were found to be the crucial associated risk factors that affect the prevalence of T. gondii infection (p < 0.05). In contrast to these, the provincial development level was found to be a confounding factor. There was no association between toxoplasmosis and household size, education attainment, and poverty in the bivariate analyses. Conclusions: The findings show that control and serological screening programs should be implemented nationwide in Turkey for the reliable and fast detection of congenital Toxoplasma infections.